2022
DOI: 10.1101/2022.06.13.495754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale structural rearrangements unleash indiscriminate nuclease activity of CRISPR-Cas12a2

Abstract: Cas12a2 is a CRISPR-associated nuclease that performs RNA-guided degradation of non-specific single-stranded (ss)RNA, ssDNA and double-stranded (ds)DNA upon recognition of a complementary RNA target, culminating in abortive infection (Dmytrenko 2022). Here, we report structures of Cas12a2 in binary, ternary, and quaternary complexes to reveal a complete activation pathway. Our structures reveal that Cas12a2 is autoinhibited until binding a cognate RNA target, which exposes the RuvC active site within a large, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…These results demonstrate that RNA targeting by SuCas12a2 causes dsDNA damage of the bacterial chromosome that in turn induces the SOS response and Abi in bacteria, reflecting a distinct mechanism of immunity that relies on indiscriminate dsDNase activity. Consistent with this observation, recent cryo-EM structures reveal Cas12a2 binds and cuts dsDNA with a mechanism completely distinct from all other CRISPR associated nucleases, while structure-guided mutants with impaired in vitro collateral dsDNase but not ssRNase and ssDNase activities abolished in vivo defense activity 20 .…”
Section: Main Textmentioning
confidence: 54%
See 2 more Smart Citations
“…These results demonstrate that RNA targeting by SuCas12a2 causes dsDNA damage of the bacterial chromosome that in turn induces the SOS response and Abi in bacteria, reflecting a distinct mechanism of immunity that relies on indiscriminate dsDNase activity. Consistent with this observation, recent cryo-EM structures reveal Cas12a2 binds and cuts dsDNA with a mechanism completely distinct from all other CRISPR associated nucleases, while structure-guided mutants with impaired in vitro collateral dsDNase but not ssRNase and ssDNase activities abolished in vivo defense activity 20 .…”
Section: Main Textmentioning
confidence: 54%
“…Investigating the underlying molecular basis of target recognition and activation of collateral cleavage by Cas12a2 could reveal new mechanisms employed by CRISPR nucleases for discriminating self from non-self targets. Recent cryo-EM structures of Cas12a2 at stages of RNA-targeting and collateral dsDNA capture are already fulfilling this need 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies showed that this ⍺-helical lid occludes the RuvC catalytic core in the binary RNA-bound Cas12a complex and opens for the accommodation of the NTS within the catalytic site. 12,30 Multi-μs long MD simulations of Cas12a after NTS cleavage show that the ⍺-helical lid establishes extensive interactions with the crRNA:TS hybrid in its open conformation (Fig. 2a-b).…”
Section: Discussionmentioning
confidence: 99%